Herbicide resistant weeds: The case of resistance to glyphosate - The Duc Ngo (Vietnam Journal of Science, Technology and Engineering, 2021)
Glyphosate has become the most widely used herbicide worldwide since 1974 with a global use of 8.6 billion kg (glyphosate active ingredient) between 1974 and 2014. This study reports on glyphosate resistant (GR) weeds and their resistance mechanisms based on global scientifically reported cases. Forty-nine different weed species have evolved resistance to glyphosate in 29 countries with a total of 318 identified cases worldwide. Fifty percent of these resistance cases were found in glyphosate-resistant cropping systems. There were 255 identified cases (80.2%) of glyphosate resistance in the top five countries (in terms of number of cases and species), namely USA, Australia, Argentina, Brazil, and Canada. The five most popular weed species (in terms of number of cases) found to be resistant to glyphosate were Conyza canadensis, Amaranthus palmeri, Amaranthus tuberculatus, Lolium perenne ssp. Multiflorum, and Ambrosia artemisiifolia with 42, 42, 29, 26, and 21 reported cases, respectively. Out of 49 weed species, 19 GR weed species were found to not only be resistant to glyphosate but also to other herbicide sites of action (multiple herbicide resistance). Glyphosate resistance mechanisms in weeds include (1) target-site alterations: target-site mutation and target-site gene amplification; and (2) non-target-site mechanisms involving different modes of exclusion from the target site: reduced glyphosate uptake, reduced glyphosate translocation, and enhanced glyphosate metabolism. It is essential to have an integrated weed management program that includes not only smart herbicide mixtures and rotations, but also cultural, manual, mechanical, and crop-based weed management methods.